2002
DOI: 10.1152/japplphysiol.00777.2001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lung liquid production in fetal sheep with blue dye dextran and radioiodinated serum albumin

Abstract: Lung liquid production and reabsorption rates and lung volumes were measured in 99 fetal sheep (119-148 days of gestation) by indicator-dilution methods with the simultaneous use of blue dye dextran (BDD) and radioiodinated serum albumin (RISA). There were no significant differences between rates of lung liquid production or reabsorption by the two methods (n = 71 pairs; paired t-test; Wilcoxon test; ANOVA); this was equally true for rates in milliliters per hour or milliliters per kilogram body weight per hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Second, we typically instill at least 50% more blue dextran, which should be sufficient to saturate all binding sites; if all binding sites are saturated with tracer, accurate estimates of lung liquid production can be made since we calculate production rates not from absolute volumes but from relative changes in volume over time. Third, we (unpublished data) and others (11,12) have used both techniques for several years and have consistently found similar estimates of lung liquid production when comparing the two.…”
Section: Discussionsupporting
confidence: 68%
“…Second, we typically instill at least 50% more blue dextran, which should be sufficient to saturate all binding sites; if all binding sites are saturated with tracer, accurate estimates of lung liquid production can be made since we calculate production rates not from absolute volumes but from relative changes in volume over time. Third, we (unpublished data) and others (11,12) have used both techniques for several years and have consistently found similar estimates of lung liquid production when comparing the two.…”
Section: Discussionsupporting
confidence: 68%
“…Although the exact volume of liquid retained within the future airways is controversial, most recent studies agree that it is 30-45 mL/kg body weight [24,25,[30][31][32], at least up until 4-5 days before labour. Some studies have reported volumes as high as 50-60 ml/kg in individual fetuses [25,31], but the large variability between studies undoubtedly reflects differences in intra-uterine conditions, which has a major impact on lung volumes [33].…”
Section: Fetal Lung Liquid Dynamicsmentioning
confidence: 99%